2002
DOI: 10.1002/cne.10169
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells in Wallerian degeneration: Morphologic and ultrastructural changes

Abstract: The morphologic and ultrastructural changes of mast cells were followed in degenerating distal and regenerating proximal stumps of frog brachial nerve during Wallerian degeneration. Quantitative analysis included determination of both number and size of mast cells. The mast cell response to injury consisted of an early and a late phase. In the early phase, there was an increase in mast cell numbers in the proximal site of the lesion and a release of Alcian blue material consistent with mediator release. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Only sporadically were some immature MC observed adhering to the blood capillaries within the brain parenchyma where they were never observed in association with neurons. Some of the MC were metachromatic with Toluidine blue and safraninpositive with AB/safranin, which indicated that the MC were mature cells as earlier described for the MC in other frog tissues (see Chieffi Baccari et al, 1998;Chieffi Baccari et al, 2003;Esposito et al, 2002). Intraperitoneal administration of T 3 and T 4 accelerates larval development; just one week after T 3 -and T 4 -injections the premetamorphic tadpoles had reached the advanced pro-metamorphic stage overlapping with the beginning of climax (stages 30-31).…”
Section: Effects Of Ptu T 3 and T 4 Treatment On Brain MC Populationsupporting
confidence: 70%
“…Only sporadically were some immature MC observed adhering to the blood capillaries within the brain parenchyma where they were never observed in association with neurons. Some of the MC were metachromatic with Toluidine blue and safraninpositive with AB/safranin, which indicated that the MC were mature cells as earlier described for the MC in other frog tissues (see Chieffi Baccari et al, 1998;Chieffi Baccari et al, 2003;Esposito et al, 2002). Intraperitoneal administration of T 3 and T 4 accelerates larval development; just one week after T 3 -and T 4 -injections the premetamorphic tadpoles had reached the advanced pro-metamorphic stage overlapping with the beginning of climax (stages 30-31).…”
Section: Effects Of Ptu T 3 and T 4 Treatment On Brain MC Populationsupporting
confidence: 70%
“…Therefore, nerve growth factor might play an important role in both perineurial and mast cell differentiation. This hypothesis is supported by the observation that the Wallerian degeneration, during which a proliferation of both perineurial and mast cells has been shown (Esposito et al, 2002;Latker et al, 1991;Olsson, 1968;Olsson and Sjostrand, 1969), is also characterized by an increase of NGF synthesis (Heumann et al, 1987). In addition, similarly to nerve cells, both mast cells (Nilsson et al, 1997;Otten et al, 1994;Tam et al, 1997) and perineurial cells synthesize and express NGF-receptors TrkA (Bronzetti et al, 1995;Ribeiro-daSilva et al, 1991;Yamamoto et al, 1992).…”
Section: Mast Cell-nerve Interactionsmentioning
confidence: 78%
“…In turn, recruited macrophages become a source of secreted cytokine and trophic factor release, inducing a complex inflammatory cascade (Stratton et al, ; Tomlinson, Zygelyte, Grenier, Edwards, & Cheetham, ). Mast cells are also recruited (Esposito, De Santis, Monteforte, & Baccari, ), orchestrating complex vascular and immune cell responses, including the chemoattraction of phagocytic neutrophils that further contribute to myelin clearance (Lindborg et al, ). In comparison, ALS nerve pathology similarly involves reactive changes in SCs (Keller, Gravel, & Kriz, ) as well as the recruitment of monocytes, macrophages, mast cells, and neutrophils (Chiu et al, ; Trias et al, ; Van Dyke et al, ).Such immune cell infiltration of the peripheral motor pathways in ALS has been linked to both protective and deleterious effects on motor neuron degeneration and disease progression (Nardo et al, ).…”
Section: Introductionmentioning
confidence: 99%